Kesiapan Petugas Berdasarkan Pengetahuan Dalam Penerapan Rekam Medis Elektronik Di Puskesmas SMB - Yunita, Nirma; Rusdiansyah, Rusdiansyah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Many obstacles occur in the implementation of electronic medical records in health facilities due to the unpreparedness of officers. The implementation of Electronic Medical Records at the SMB Health Center is in the transition stage using the E-Puskesmas application. The use of the E-Puskesmas application has not been fully implemented because officers are constrained in understanding how to fill out the form on the E-Puskesmas application and their skills in using computers are still lacking. The purpose of this study was to determine the readiness of officers based on their knowledge in the implementation of electronic medical records at the SMB Health Center. The type of quantitative research is a descriptive approach, the sampling technique uses total sampling and the research instrument is a questionnaire. Most of the knowledge is good as many as 6 people (93.2%) and knowledge is lacking as many as 2 people (6.8%) about electronic medical records in general and has legal value at the SMB Health Center. Officers need to attend training and seminars on electronic medical records to improve their knowledge in supporting their work.